Diarylamine/diarylnitroxide cycle: quantum chemical and electrochemical estimation - Levitskiy, Oleg A.; Sentyurin, Vyacheslav V.; Magdesieva, Tatiana V. (Heliyon, 2019)
Possibility for diarylamine/diarylnitroxide cycling via electrochemical N–O bond formation/bond breaking processes was considered using quantum-chemical and electrochemical methods. It was shown that electrochemically reduced diarylnitroxides undergo fast N–O bond cleavage in the presence of oxophilic Li ions. The possible reaction scheme was suggested. In contrast, in the presence of Na+ salts, aminoxyl anions are stable and can be considered as possible anodic redox active material in energy storage systems utilizing Na+ ions migration. Direct oxygenation of diarylaminyl radicals with dioxygen yielding diarylnitroxide is not feasible; multiple competing routes involving the aromatic moiety are observed instead. The results obtained shed light on possibilities and limitations for functioning of nitroxide-based redox active electrode materials. Electrochemistry; Organic chemistry; Theoretical Chemistry; electrochemical bond cleavage; diaryl nitroxides; redox materials; electrode reactions; specific solvation